The Inhibitory Effect of Ginger Extract on Ovarian Cancer Cell Line; Application of Systems Biology - Roghiyeh Pashaei-Asl; Fatima Pashaei-Asl; Parvin Mostafa Gharabaghi; Khodadad Khodadadi; Mansour Ebrahimi; Esmaeil Ebrahimie; Maryam Pashaiasl (Tabriz University of Medical Sciences, 2017)
Purpose: Ginger is a natural compound with anti-cancer properties. The effects of ginger and its mechanism on ovarian cancer and its cell line model, SKOV-3, are unclear. In this study, we have evaluated the effect of ginger extract on SKOV-3. Methods: SKOV-3 cells were incubated with ginger extract for 24, 48 and 72 hours. Cell toxicity assay was performed. Different data mining algorithms were applied to highlight the most important features contributing to ginger inhibition on the SKOV-3 cell proliferation. Moreover, Real-Time PCR was performed to assay p53, p21 and bcl-2 genes expression. For co-expression meta-analysis of p53, mutual ranking (MR) index and transformation to Z-values (Z distribution) were applied on available transcriptome data in NCBI GEO data repository. Results: The ginger extract significantly inhibited cancer growth in ovarian cancer cell line. The most important attribute was 60 µg/ml concentration which received weights higher than 0.50, 0.75 and 0.95 by 90%, 80% and 50% of feature selection models, respectively. The expression level of p53 was increased sharply in response to ginger treatment. Systems biology analysis and meta-analysis of deposited expression value in NCBI based on rank of correlation and Z-transformation approach unraveled the key co-expressed genes and co-expressed network of P53, as the key transcription factor induced by ginger extract. High co-expression between P53 and the other apoptosis-inducing proteins such as CASP2 and DEDD was noticeable, suggesting the molecular mechanism underpinning of ginger action. Conclusion: We found that the ginger extract has anticancer properties through p53 pathway to induce apoptosis.